Unpacking the Dimensions of Augmented Reality, Digital Influencers and Brand Loyalty: Hybrid Approach of Bibliometric Analysis and Systematic Literature Review - Sri Mulyati; Popy Rufaidah (Green Publisher Indonesia, 2025)
This research highlights the dimensions involved in each variable that emerged from previous studies and identifies the indicators associated with the dimensions of augmented reality, digital influencers, and brand loyalty. It employs Publish or Perish and VOSviewer software for bibliometric analysis. The data sources include Scopus, ScienceDirect, Emerald Insight, Sage, and SpringerLink. The findings reveal similar and distinct dimensions and indicators for augmented reality, digital influencers, and brand loyalty. Similarities appear in the augmented reality dimensions related to experience, effect, interactivity, and vividness. Digital influencers relate to effectiveness, characteristics, attractiveness, authenticity, credibility, parasocial relationships, sponsorship, original value, persuasiveness, power, trust, and uniqueness. Brand loyalty relates to indicators such as willingness and purchase intention. The bibliometric maps reveal new variables and indicators for measuring augmented reality, digital influencers, and brand loyalty. This research model can be extended by combining variables, dimensions, and indicators as recommendations for future studies, with implications for researchers and practitioners in marketing. These findings offer practical implications for researchers developing comprehensive measurement instruments and for practitioners designing integrated marketing strategies that leverage augmented reality technology and digital influencer engagement to enhance brand loyalty.